Applying Theory Of Planned Behaviour In Predicting House Purchase Intention In Gaza Strip - Sbakhi, Bissan M. E. (2019)
Factors affecting residential houses purchase intention are of great importance worldwide. This study aims at determining the factors affecting the purchasing intention for residential houses in Gaza Strip. Following the Ajzen theory of planned behaviour, the study examined different factors which are attitude, friends influence, parents influence, spouse influence, children influence, perceived behavioural control and housing service quality. Also, the study examines if the refugee status (refugee and non-refugee status) moderates towards purchase intention. While previous studies have investigated many aspects of the purchase intention of home buyers worldwide, studies have a limited understanding of the residential houses purchase intention among people in Gaza Strip. The data collection method of email survey was used in this research. A questionnaire was developed using items taken from previous studies applied specifically in Gaza Strip. Based on 270 questionnaires, the data was analysed using SPSS version 20 and PLS-SEM software. The results show that attitude, friends influences, children influence, parents influences, perceived behaviour control and service quality affect the housing purchase intention, while moderating variable did not moderate the relationship between attitude, perceived behaviour control, service quality and purchase intention. This study contributes to an improved understanding of home buyers in Gaza. It is expected that the results of the survey will provide information on the intention to purchase houses and which variables affect buyers’ intention.